Detection of Chlamydia infection in Peromyscus species rodents from sylvatic and laboratory sources. Issue 3 (4th January 2016) - Ramsey, Kyle H.; Sigar, Ira M.; Schripsema, Justin H.; Townsend, Kathryn E.; Barry, Randall J.; Peters, Jan; Platt, Kenneth B.
Abstract : To determine if Chlamydia muridarum, or other chlamydiae, are enzootic in rodents, we probed a serum bank of wild Peromyscus spp. mice for immunoglobulin G-antibody reactivity to ultraviolet light-inactivated C. muridarum elementary bodies (EBs) using an enzyme-linked immunoassay. Applying a cut-off for a positive reaction of OD405 nm = 0.1 at a 1:20 dilution, we found titratable antibody reactivity in 190 of 247 specimens surveyed (77%, mean OD405 = 0.33 ± 0.26, range = 0.11–1.81, median = 0.25). In addition, serum samples were obtained from a colony of specific pathogen-free Peromyscus spp. maintained at the University of South Carolina and six of 12 samples were reactive (50%, mean OD405 = 0.19 +/− 0.08, range = 0.1–0.32, median = 0.18). Lastly, 40 additional wild Peromyscus spp. were captured in a disparate region of Midwestern USA and 22 serum specimens were reactive (55%, mean OD405 = 0.22 +/− 0.11, range = 0.1–0.48, median = 0.2). Specificity of selected reactive sera for chlamydial antigen was confirmed on Western blot using resolved purified EBs as the detecting antigen. From tissues removed from several mice at necropsy, the gene for chlamydial 16S ribosomal ribonucleic acid (rRNA) was amplified by polymerase chain reaction (PCR). Positive samples of 16S rRNA were subjected to additional PCR for the major outer membrane protein gene ( omp A). The amplicons of three select omp A positive samples were sequenced with ≥99% homology with C. muridarum. Our findings indicate that chlamydial infection is enzootic for Peromyscus spp., and that C. muridarum, or a closely related species or strain, is likely the agent in the tested rodent species. Abstract : Peromyscus species are commonly infected with chlamydiae.